Aktivitas Antihiperkolesterolemia Ekstrak Batang Dan Akar Kemangi Hutan (Ocimum sanctum) Pada Tikus Putih - Magi Melia; Maria Astriyani Adeodatus; Yohana Krisostoma Anduk Mbulang (Jurnal Farmasi & Sains Indonesia, 2021)
Hypercholesterolemic is a condition characterized by an increase in fasting Low Density Lipoprotein (LDL) levels without an increase in triglyceride levels and a decrease in HDL (High Density Lipoprotein) levels. Ocimum Sanctum is a plant that can be used as an alternative anti-hypercholesterolemic treatment because it contains alkaloids, flavonoids, tannins, saponins, triterpenoids, and eugenol. The objective of this study is to determine the anti-hypercholesterolemic activity and to determine the most effective dose of extracts of stems and roots of Ocimum sanctum, which can show anti- hypercholesterolemic effects in white rats. A total of 25 male white rats were divided into 5 groups. Group I (simvastatin 0.18 mg / 200gr BW), group II (0.5% Na CMC), groups III, IV and V (extracts of stems and roots of Ocimum sanctum with their respective doses of 50 mg / kgBW, 75 mg / kgBW and 100 mg / kgBW) and measured LDL and HDL cholesterol levels using the Direct and Indirect methods. The data obtained were analyzed using ANOVA. The results of statistical analysis showed that there was an anti-hypercholesterolemic effect at the three doses of extracts of stems and roots of Holy Basil (Ocimum Sanctum). The best dose in reducing LDL and increasing HDL compared to simvastatin is 100 mg / KgBW.